Management of posterior cruciate ligament avulsion by cannulated screw fixation - Lamichhane, A; Mahara, DP (Journal of Institute of Medicine Nepal, 2013)
Introduction: Posterior cruciate ligament (PCL) is the main posterior stabilizer of the knee. The PCL also plays a role as a central axis controlling and imparting rotational stability to the knee. The most effective management of posterior cruciate ligament (PCL) injuries remains unclear and the natural history of untreated PCL injuries is controversial. The need for surgical repair of displaced bony PCL avulsions is less controversial. Here we present repair of PCL avulsion by screw fixation. Methods: There were total of 18 patients (Male 12 and Female 6) operated for isolated PCL avulsion from tibia during the period from 2002 to 2010. Preoperative evaluation was done clinically and radiologically .MRI was advised for suspected other ligaments and meniscal injuries. Patients with other ligaments and meniscal injury were not included in this series. All cases operated by simplified approach described by Burks and Schaffer. Avulsed fragment was reduced and xed with 4 mm a cannulated screw. Evaluation of the patients were done clinically, radilologically and using functional scale of Tegner-Lysholm. Results: Out of 18 patients, 12 patients were male and 6 patients were female. Average age of the patients was 29yrs (range 18-47 yrs). Average period of follow up was 31 months (ranging 12 - 52 m). Range of movement was found full in all patients at the last follow up. Grade 1-2 laxity was found in 8 patients but subjectively they were not aware of the laxity. Average Lysholm score was 91 (range 87-97). Conclusion: Improvised approach by Burk and Schaffer is safer and easier than the classical one. Open reduction and fixation with cannulated screw is one of the excellent techniques for tibial avulsion of posterior cruciate ligament. DOI: http://dx.doi.org/10.3126/joim.v34i3.8914 Journal of Institute of Medicine, December, 2012; 34:28-31